Proper Milking Procedures - Izabella Toledo (EDIS, 2021)
These brochures illustrate steps to optimize milking efficiency and milk quality as well as the importance of environmental management in barns and milking parlors. Written by Izabella Toledo, and published by the UF/IFAS Department of Animal Sciences, November 2021.